Determinants of family employee work performance and compensation in family businesses - S. P. Van Der Merwe (South African Journal of Business Management, 2009)
This study highlighted the importance of establishing clear work roles and responsibilities in the family business, the measurement of family employee work performance and regular feedback on their performance and fair and market-based compensation of family employees in family businesses. An Oblimin oblique rotation was performed on the principal components of the exploratory factor analysis. In this study three factors describing the theoretical dimensions of family employee work performance, clear work roles and responsibilities and family employee compensation in family businesses were extracted. Although statistical significant differences were found between the perceptions of male and female as well as between senior and younger generation family employees regarding the constructs, these differences were not practically significant. This study, however, confirms the important role that an effective family employee work performance management and compensation strategy plays to ensure harmonious family relationships and at the end the sustainability of the family business. Practical recommendations are suggested to improve the effectiveness of family employee work performance and compensation in family businesses. Recommendations are also offered to utilise the questionnaire as a diagnostic tool.
Keywords: 650